2019
DOI: 10.1002/hep.30198
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Specificity Phosphatase 9 Protects Against Nonalcoholic Fatty Liver Disease in Mice Through ASK1 Suppression

Abstract: Non-alcoholic fatty liver disease (NAFLD), ranging from non-alcoholic fatty liver (NAFL) to non-alcoholic steatohepatitis (NASH), is the leading cause of chronic liver diseases. Until now, no medications for NAFLD have been approved by relevant governmental agencies. Dual-specificity phosphatase 9 (Dusp9) is a member of the DUSP protein family. Dusp9 is expressed in insulin-sensitive tissues, and its expression may be modified with the development of insulin resistance (IR). However, the molecular targets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 37 publications
1
57
0
Order By: Relevance
“…As a MAPKKK, ASK1 acts as a master switch of cell death: it initiates and sustains activation of two MAPKs (p38 and JNK) to induce apoptosis. Since ASK1 is over‐activated in liver tissues during NAFLD, ASK1 critically involved in liver inflammation and thought to be an ideal druggable target of NAFLD . Based on our findings, inhibition on the activation of ASK1 pathway and its downstream JNK and p38 signals by melatonin could be a promising strategy to alleviate NAFLD.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As a MAPKKK, ASK1 acts as a master switch of cell death: it initiates and sustains activation of two MAPKs (p38 and JNK) to induce apoptosis. Since ASK1 is over‐activated in liver tissues during NAFLD, ASK1 critically involved in liver inflammation and thought to be an ideal druggable target of NAFLD . Based on our findings, inhibition on the activation of ASK1 pathway and its downstream JNK and p38 signals by melatonin could be a promising strategy to alleviate NAFLD.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, ASK1 is involved in the development of various diseases, including tumorigenesis, neutrophilic dermatosis, cardiac hypertrophy, diabetes, and acquired immunodeficiency syndrome . For the past few years, several investigations have showed that ASK1 is continuously over‐activated in liver during NAFLD progression, and inactivation of ASK1 might remedy NAFLD . A very recent clinical study showed that a selective ASK1 inhibitor reduced liver fibrosis in patients with NASH …”
Section: Introductionmentioning
confidence: 99%
“…Cornell et al demonstrated that Dusp4 deficiency in macrophages reduces the secretion of proinflammatory and anti‐inflammatory cytokines through the MAPK signaling pathway . Dusp9 played a key role in the development of NAFLD . Owing to the different cell types and research contents, the effect of dusp26 on MAPK was variable.…”
Section: Discussionmentioning
confidence: 99%
“…Dusp9, a member of the DUSP protein family, was down‐regulated in the mitogen‐activated protein kinase (MAPK) pathway to regulate differentiation, proliferation, and apoptosis through a series of cellular responses. Dusp26 was reported to inhibit the phosphorylation of p38 to block p38‐mediated apoptosis in some types of tumor cells . We hypothesized that Dusp26 may play a critical role in the lipid accumulation and obesity‐associated inflammation in liver cells during the progression of different stages of NAFLD.…”
mentioning
confidence: 98%
“…Compared to untreated immortalized hepatocytes, DUSP12 expression levels are also lower in hepatocytes cultured in the presence of palmitic acid and oleic acid, the most abundant fatty acids in Western diets. Intriguingly, it has been recently shown that the expression of two related DUSP proteins, DUSP9 and DUSP26, is down‐regulated in the liver of mice with hepatic steatosis, underscoring the important role of the DUSP proteins in the pathogenesis of liver diseases.…”
mentioning
confidence: 99%